Passer de l'élite économique à l'élite politique grâce à l'action diplomatique: Le cas des Juifs « portugais » de Hambourg de la fin du XVIIe siècle au début du XVIIIe siècle - Félicite, Indravati (Histoire Urbaine, 2014)
While the careers of the "court Jews" and their importance for the building of an administration in the early modern German principalities have received extensive treatment in scholarly literature, the role played by Sephardic Jews in the diplomacy of the Holy Roman Empire has rarely attracted much historical interest. This paper deals with the group of "Portuguese Jews" that settled down in Hamburg at the beginning of the 17th century. Some of them became the diplomatic representatives of the kings of Sweden, Denmark, Poland, and even France. The career paths of two members of this community, Jacob Abensur and Diego Teixeira, allow us to see that the diplomatic service offered opportunities for social advancement. However, these opportunities also aroused strong opposition among the city's elite and "middle class", which can be interpreted as the sign of an identity and of a social crisis of the Hanseatic town at the turn of the 18th century.
CRIS-Team Scopus Importer:2024-04-04